Globalization, Redemocratization and the Philippine Bureaucracy - Mirshariff Tillah (Philippine Institute for Development Studies (PIDS), 2005)
The increasing demands and expectations placed upon the Philippine bureaucracy by a redemocratizing society are further amplified by the strengthening of global institutional pressures emanating from organizations such as the World Trade Organization and the Asia Pacific Economic Cooperation. These forces converge to advocate a minimal and more effective government through downsizing, privatization, deregulation, decentralization, harnessing civil society and private sector capacities, empowering citizens, and adopting a customer orientation. These have led to significant changes in the very nature and role of the civil service, how it is managed, and the means by which administrative reform can be achieved. This study thus looks into the impact of globalization on the Philippine bureaucracy in a redemocratizing context. In order to observe these changes, three agencies have been selected as case studies–the Departments of Trade and Industry, Agriculture, and Foreign Affairs.
Keywords: 330; globalization; governance; civil society; redemocratization; Philippine bureaucracy; Globalisierung; Bürokratie; Gesellschaft; Philippinen; Governance-Ansatz; Demokratisierung